The mobilizing and protective role of national identification in normative and non‐normative collective action - Stathi, S.; Vezzali, L.; Waldzus, S.; Hantzi, A. (Journal of Applied Social Psychology, 2019)
In the context of the financial crisis in Europe and drawing on social identity and perceived disadvantage literature, this research explored national identification, perceived prejudice, perceived ostracism, and anger as predictors of intentions to engage in normative collective action and support for non‐normative and destructive action. Correlational data were collected in Greece (N = 218), Portugal (N = 312), and Italy (N = 211) during the financial crisis that affected several European countries in the early 2010s. Hierarchical regressions showed that national identification, above and beyond all other variables, positively predicted normative collective action intentions, and negatively predicted support for non‐normative action. That is, people who were identified more strong with their national identity were more likely to report that they will engage in collective action to enhance the position of their (national) in‐group, and less likely to support destructive collective action. Mediation analyses revealed that in the case of Portugal and Italy, national identification associated negatively with anger, while anger positively predicted normative collective action. The findings of this research point to the importance of national identification as a factor, that, on the one hand motivates people's mobilization toward supporting the rights of the ingroup but on the other hand impedes the more negative and destructive side of collective action. The contextual and instrumental role of national identity in contexts of threat is discussed.